Determination of amino acids by capillary and microchip electrophoresis with contactless conductivity detection - Theory, instrumentation and applications - Tůma, Petr (Talanta, 2021)
This review article summarises aspects of the determination of amino acids using capillary and chip electrophoresis in combination with contactless conductivity detection from their historical beginnings to the present time. Discussion is included of the theory of conductivity detection in electromigration techniques, the design of contactless conductivity cells for detection in capillaries and on microchips, including the use of computer programs for simulation of the conductivity response and the process of the electrophoretic separation of amino acids. Emphasis is placed on optimisation of the background electrolyte composition, chiral separation, multidimensional separation, stacking techniques and the use of multidetection systems. There is also a description of clinical applications, the determination of amino acids in foodstuffs, waters, soils and composts with emphasis on modern techniques of sample treatment, such as microdialysis, liquid membrane extraction and many other techniques.
Keywords: Capillaries; Clinical analysis; Sample treatment; Food analysis; elektrická vodivost; Electrophoresis, Capillary; elektroforéza mikročipová; Microchip electrophoresis; elektroforéza kapilární; aminokyseliny; Amino Acids; Electrophoresis, Microchip; Capillary electrophoresis; Amino acid; Electric Conductivity; Contactless conductivity detection; Stacking; Microdialysis; kapiláry